Salt origin and their saltiness: A time-intensity sensory characterization - Lan, Nguyen Huu; Huong, nguyen Thi Ngoc; Thinh, Pham Huu; Doan, Ngoc Thuc Trinh; Dat, Lai Quoc; Dung, Nguyen Hoang (Vietnam Journal of Science and Technology, 2023)
Excessive salt consumption has been found to cause many negative effects on human health. To date, many researches have been conducted to reduce the sodium content of the diet. This study focused on the comparison of saltiness intensity and other parameters in time-intensity curves of four commercial grain salts in four regions of Viet Nam (Bac Lieu, Thanh Hoa, Sa Huynh, Vung Tau), one flower salt in Sa Huynh and a control sample with two particle sizes of 1-2 mm and 2-3 mm to find out their taste perception characteristics. A modified sensory evaluation technique focusing on time-intensity was used to train a panel to evaluate the temporal profile of saltiness of salt crystals. The results showed a significant difference in the perception ability and time intensity of saltiness in salt products by region and particle size. Sensory measures exhibited the differences in the specificity of salt samples by region and a strong correlation with their physical properties. Sa Huynh flower salt and sea salt showed different characteristics compared to other salt samples with higher intensity of salty taste, faster time to reach the maximum intensity, and shorter duration of salt taste intensity. These results demonstrated that flower salt could reduce the level of sodium intake while maintaining the saltiness perception in products, which is a potential ingredient in food, spices, etc.